دور التصميم الجرافيكي في بناء العلامة التجارية للأزياء - عيادي, خديجة (كلية الأدب العربي والفنون, 2025)
يتلخص هذا البحث بعنوان "دور التصميم الجرافيكي في بناء العلامة التجارية للأزياء" في أهمية التصميم الجرافيكي في خلق ماركة ناجحة، ذات صيت واسع. بحيث يكمن ذلك بتطبيق قوانين الجرافيزم على تلك التصاميم البصرية كصور جامدة أو حركية هادفة، بطريقة تؤثر على تصرفات المستهلك وعاطفته بطريقة إيجابية، لكسب جمهور كبير والتفوق في ساحة صناعة الأزياء. وبذلك تكون علاقة المجالين قوية مترابطة. وخلال هذا يتسع عالم الجرافيزم ويتسم بالقوة والسلطة في المجال التجاري للحاجة الدائمة له. This research, titled “The Role of Graphic Design in Building a Fashion Brand”, summarizes the importance of graphic design in creating a successful and widely recognized brand. This is achieved by applying the principles of graphisme to visual creations static or animated in a purposeful way that influences the consumer behavior and emotions positively, in a way helping attract a large audience and excel in the market of the fashion industry. And so, the relationship between these two fields is strong and interconnected. As a result, the world of graphic design continues to expand, gaining strength and authority in the commercial realm due to the constant need for it.
Keywords: التصميم الجرافيكي، تصميم الأزياء، علامة تجارية، التسويق والترويج; graphic design, fashion design, trademark, marketing, promotion.